Ideals generated by quadrics - Hong, Jooyoun; Simis, Aron; Vasconcelos, Wolmer V (Journal of Algebra, 2015)
Our purpose is to study the cohomological properties of the Rees algebras of a class of ideals generated by quadrics. For all such ideals I⊂. R=. K[. x, y, z] we give the precise value of depth. R[. It] and decide whether the corresponding rational maps are birational. In the case of dimension d≥. 3, when K=R, we give structure theorems for all ideals of codimension d minimally generated by (d+12)-1 quadrics. For arbitrary fields K, we prove a polarized version. © 2014 Elsevier Inc.
Keywords: Associated graded ring; Castelnuovo regularity; Hilbert coefficients; Primary; Rees algebra; Relation type; Secondary; dept.mat; peer-reviewed